La indagación previa y su sujeción a los principios constitucionales en el debido proceso - Racines Tobar, Diego Fernando (2013)
This study is a doctrinal approximation into application and accomplishment of rights and principles of due process during all criminal process periods, specifically its attention during the Previous Investigation phase. It contains a brief study about the segments and phases that criminal trial has and Penal Process Code enunciates, with doctrinal focus it refers to each period, its own objective, proper characteristics, among other concepts. In this order, it contains the process distinctive periods, particularly the previous investigation phase, prior to prosecutor investigation; its objective is to accumulate all possible evidences to impulse a penal trial